2011
DOI: 10.1111/j.1553-2712.2011.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Career Selection in American Emergency Medicine Residents

Abstract: Background: The future of academic emergency medicine (EM) is based on the continued successful recruitment and cultivation of new faculty from EM residents. Little data exist as to the current rate of residents initially choosing an academic career path or which residency programs are best situated to result in new faculty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 16 publications
4
35
0
Order By: Relevance
“…During residency, mentoring is viewed as beneficial for career planning, specialty selection, and most notably, the pursuit of academic careers [8,12-16]. However, prior studies indicate that a large proportion of residents lack mentors [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…During residency, mentoring is viewed as beneficial for career planning, specialty selection, and most notably, the pursuit of academic careers [8,12-16]. However, prior studies indicate that a large proportion of residents lack mentors [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…1 Preliminarily, scholarly tracks seem to be successful -greater academic productivity during residency has been correlated with a greater number of residents choosing academic careers. 5 Some success has also been shown with measuring outcomes of scholarly tracks in other specialties-an obstetrics track at a family medicine residency program found that its residents performed similarly to obstetrics and gynecology residents on examination scores and number of procedures performed, 6 and a new global health track at a different program achieved high scores on resident evaluations. 7 Deficiencies can also be identified-a pediatrics residency with a primary care specialty track found that graduates did not express universally high levels of comfort with all areas of pediatrics emphasized by the track.…”
mentioning
confidence: 99%
“…These overall values are consistent with a recent study conducted 3 years prior to ours, which reported that 26.1% of residents choose academic careers. 8 With regard to challenges and obstacles to resident research, difficulties with study design and data collection were ranked above all others. In terms of opportunities for improvement, respondents strongly supported the development of online study design and biostatistics modules, while giving less support to activities that are regularly provided by their residency programs, such as online journal clubs and mentorship.…”
Section: Discussionmentioning
confidence: 99%
“…8 The questions were refined and pilot-tested online by the subcommittee and independent academic faculty.…”
Section: Survey Content and Administrationmentioning
confidence: 99%
See 1 more Smart Citation